How to define chronic prurigo?. Issue 12 (6th June 2019) - Pereira, Manuel P.; Ständer, Sonja
Abstract: Chronic prurigo impairs quality of life and is immensely challenging to treat. Until recently, no clear definition or classification system was available for this disease. A European task force specialized in pruritus defined chronic prurigo as a distinct disease characterized by chronic pruritus, a lengthy scratching behaviour and the presence of pruriginous lesions. Papular, nodular, plaque, umbilicated and linear prurigo were identified as clinical subtypes according to the most prominent lesion type observed in the physical examination. Various clinical and pathophysiological aspects, which are common across the range of clinical manifestations of chronic prurigo, argue for chronic prurigo as a disease in its own right. Chronic prurigo should be clearly demarcated from other conditions such as so‐called acute or subacute prurigo forms as well as from psychogenic self‐inflicted skin lesions, since different diagnostic criteria apply for these diseases. This viewpoint essay provides a detailed definition and classification of chronic prurigo including its obligatory and associated diagnostic criteria and discusses chronic prurigo as a distinct disease as well as the demarcation to other relevant conditions.